1998
DOI: 10.1038/bjc.1998.486
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in lung cancer

Abstract: Summary More research and new treatment options are needed in all stages of lung cancer. To this end immunotherapy needs a revival in view of recent improved technologies and greater understanding of the underlying biology.In this review we discuss mechanisms of tumour immunotherapy, non-specific, specific and adoptive, with particular reference to a direct therapeutic action on all subtypes of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…Therapeutic vaccination using nonspecific immunostimulants, e.g. intradermal BCG, has been tested in randomized clinical trials in lung cancer, but a clear benefit has never been shown for its use (Al-Moundhri et al, 1998).…”
mentioning
confidence: 99%
“…Therapeutic vaccination using nonspecific immunostimulants, e.g. intradermal BCG, has been tested in randomized clinical trials in lung cancer, but a clear benefit has never been shown for its use (Al-Moundhri et al, 1998).…”
mentioning
confidence: 99%
“…Early studies on Calmette-Guerin adjuvant Calmette-Guerin adjuvant and neoadjuvant bacillus vaccine therapy were negative [21,22].…”
Section: Vaccines Against Cancermentioning
confidence: 99%
“…This may be because early immunotherapy approaches, including firstgeneration vaccines, IL-2 and interferon, were not target specific and were highly toxic. [29][30][31][32] As reviewed by Al-Moundhri et al, 29 lung cancer trials testing vaccination with Corynebacterium parvum or treatment with levamisole, an immunostimulant, showed limited or no benefit with these interventions. In addition, across numerous trials, no clear benefit was demonstrated with either IL-2 treatment alone, IL-2 plus lymphokine-activated killer (LAK) cells, or IL-2 plus melatonin.…”
Section: The Immune System As a Target For Cancer Therapy: Historicalmentioning
confidence: 99%
“…Similarly, interferon alone or in combination with IL-2 or chemotherapy did not demonstrate significant activity in patients with lung cancer. 29 The reported toxicities with IL-2 and LAK cells included capillary leak syndrome, hepatic and renal dysfunction, and life-threatening cardiac and pulmonary toxicities. 31 Interferon-associated toxicities include hematologic disturbances, neurological symptoms including depression, hepatic dysfunction, and rare but severe cardiotoxicities.…”
Section: The Immune System As a Target For Cancer Therapy: Historicalmentioning
confidence: 99%